The Greek crisis: A story of self-reinforcing feedback mechanisms - Katarina Juselius; Sophia Dimelis (Kiel Institute for the World Economy (IfW), 2018)
While there seems to be a well-established consensus about the underlying causes to the Greek crisis, less is known about internal and external transmission mechanisms that ultimately caused unemployment to increase rapidly over this period. Motivated by the structural slumps theory in Phelps (Structural slumps, 1994), the paper attempts, therefore, to uncover the dynamic mechanisms behind prices, interest rates, and external imbalances that contributed to the severity and the length of the crisis. The authors find that the strongly increasing real bond rate and unemployment rate together with a persistently appreciating real exchange rate and a deterioration of competitiveness in the euro-zone have contributed to persistently growing structural imbalances in the Greek economy. As the lack of confidence in the Greek economy grew steadily, the scene was set for a monumental structural slump. Over the crisis period, all variables exhibited self-reinforcing feedback adjustment somewhere in the system except for inflation rate. Unemployment took the burden of adjustment when the bond rate sky rocketed, competitiveness deteriorated, and confidence fell.
http://dx.doi.org/10.7910/DVN/EAABYT
Keywords: C32; E24; E31; E65; 330; Greek crisis; unemployment; CVAR analysis; structural slumps; nonconstant natural rate; self-reinforcing adjustment